Effect of Financial Management Practices and Budget Absorption in the County Government of Nakuru, Kenya - Wakanyi, Newton Karanja (My University, 2025)
Abstract An effective budgetary process in the county government is necessary because it helps the county treasury estimate revenue and expenditures from funds received from the national Government and funds collected by the county government. However, the budgeting process in county governments in Kenya has faced challenges, thereby hindering the achievement of the anticipated development. Therefore, this study sought to determine the effect of financial management practices on budget absorption in the County Government of Nakuru. Specifically, the study sought to assess the impact of financial reporting practices, cash flow management practices, capital expenditure planning practices, and cost control practices on budget absorption in the County Government of Nakuru. The study was anchored in agency theory, liquidity preference theory, pecking order theory, and transaction cost economics. The study adopted a descriptive research design. The total target population was 87 employees, comprising 10 County Executive Committee Members, 10 Chief officers, 7 directors in the County treasury, 21 County treasury staff, 28 accountants from County entities/departments, and 11 Sub-County administrators. The study adopted a census technique to include all 87 targeted respondents. The study relied on primary data collected through a questionnaire. A pilot study was conducted in Kericho County Government, where 9 questionnaires were distributed to officers at the county treasury. Both descriptive and inferential statistics were utilized. Descriptive statistics included percentages, frequencies, mean, and standard deviation. Inferential statistics involved the use of correlation and regression analysis. Findings revealed that a unit increase in financial reporting practices led to a 0.619-unit improvement in budget absorption. Furthermore, the findings revealed that a unit increase in cash flow management practices led to a 0.379-unit increase in budget absorption. In addition, the finding revealed that a unit increase in capital expenditure planning practices led to a 0.794-unit increase in budget absorption. Finally, the findings indicated that a unit increase in cost control practices led to a 0.468-unit improvement in budget absorption. The study concluded that there was a positive, statistically significant correlation between financial reporting practices, cash flow management practices, capital expenditure planning practices, and cost control practices and budget absorption. Based on the findings, the study recommended that the County Government of Nakuru strengthen its financial reporting practices by ensuring timely, transparent, and accurate reporting systems that enhance accountability and improve budget absorption. In addition, the County should implement effective cash flow forecasting and monitoring mechanisms to guarantee that funds are readily available when required for project execution. Furthermore, adopting comprehensive, realistic capital expenditure planning will be essential to align projects with available resources and set implementation timelines, thereby improving efficiency. Lastly, the County should enhance its cost control measures by regularly monitoring expenditures and strictly adhering to budgetary allocations, minimizing waste, and optimizing the use of available resources.
Full text
Keywords: Financial Reporting Practices; Cash Flow Management Practices; Capital Expenditure Planning Practices; Cost Control Practices; and Budget Absorption.